2006
DOI: 10.1620/tjem.209.61
|View full text |Cite
|
Sign up to set email alerts
|

Successful Autologous Peripheral Blood Stem Cell Transplantation Using Thiotepa in a Patient with Systemic Sclerosis and Cardiac Involvement

Abstract: A 19-year-old man with systemic sclerosis (SSc) was hospitalized for autologous peripheral blood stem cell transplantation (auto-PBSCT) due to progressive scleroderma and cardiac involvement despite conventional treatment. During the administration of cyclophosphamide (60 mg/kg/day for 2 days) for mobilization and collection of CD34 + selected peripheral blood stem cells, he developed congestive heart failure. Echocardiogram showed hypokinetic asynergy from the septum to posterior wall, which might indicate un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…). Nine additional studies were identified by manual searching . We first removed 119 duplicates and then screened the abstracts before excluding an additional 226 studies because of irrelevance.…”
Section: Resultsmentioning
confidence: 99%
“…). Nine additional studies were identified by manual searching . We first removed 119 duplicates and then screened the abstracts before excluding an additional 226 studies because of irrelevance.…”
Section: Resultsmentioning
confidence: 99%
“…Komatsuda et al described HSCT applied to a patient with cardiac involvement using thiotepa and cyclophosphamide in small doses (100 mg/kg) as a conditioning regimen. There was no toxicity during transplantation and the patient was in disease remission (33) .…”
Section: Autologous Hematopoietic Stem Cell Transplantation: Internatmentioning
confidence: 96%
“…Não houve toxicidade durante o transplante e o paciente obteve remissão da doença. 22 Como avaliar a função cardíaca do paciente com esclerose sistêmica?…”
Section: Qual Regime De Condicionamento Não Mieloablativo?unclassified